The visual dictionary of illustration - Wigan, Mark (AVA Publishing SA, 2009)
"This book is a guide to the many and varied terms used frequently within illustration. From abstraction to Zeitgeist, picture books to the poster, this book will prove an invaluable resource to anyone interested in the art of illustration. Each term is explained and contextualised, giving the reader an enhanced understanding of illustration terminology." -- Provided by publisher.